TRANSMISI BUDAYA MASYARAKAT ADAT BATAK TOBA DALAM PERGELARAN BUDAYA ULAON UNJUK DI TAPANULI UTARA - Tama, Krisna; Sathotho, Surya Farid; Sahid, Nur (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2024)
This research examines the Ulaon Unjuk ritual in Sigotom Julu on December 2, 2022, with the aim of analyzing the performance elements and the cultural values transmitted through its execution. Ulaon Unjuk is a traditional marriage ritual of the Batak Toba community, which plays a crucial role in fulfilling the existential goals of hagabeon (prosperity in descendants), hamoraon (wealth), and hasangapon (honor). To this day, the Ulaon Unjuk ritual remains a mandatory practice to ensure that the bride and groom receive social validation as members of the Batak Toba indigenous community. As a marriage ritual, Ulaon Unjuk constitutes a cultural performance that encompasses elements of a staged event and facilitates the transmission of cultural values. This study employs a qualitative ethnographic approach for data collection, with the data subsequently analyzed narratively and inductively using a cultural performance framework. The findings are documented through ethnographic writing techniques. The results reveal that the Ulaon Unjuk ritual is carried out according to specific sequences and rules, is non-productive in nature, utilizes symbolic objects, and involves a designated performance space. These findings imply that Ulaon Unjuk includes performative aspects akin to theater. The ritual also incorporates the concept of Dalihan Na Tolu, which is central to the cultural values of the Batak Toba community, encompassing aspects such as patrilineality, clan (marga), marhobas (mutual assistance), tudu-tudu sipanganon (sharing of food), jambar (division of ritual objects), marsisisean (mutual respect), ulos (traditional cloth), tortor (traditional dance), tandok (ritual container), and others. In conclusion, the Ulaon Unjuk ritual represents a cultural performance that embodies theatrical elements and transmits the cultural values of the Batak Toba indigenous community through its enactment.Keywords: Batak Toba, Cultural Transmission, Dalihan Na Tolu, Ulaon Unjuk